2018
DOI: 10.1159/000486453
|View full text |Cite
|
Sign up to set email alerts
|

Rotational Thromboelastometry Helps to Reduce Blood Product Consumption in Critically Ill Patients during Small Surgical Procedures at the Intensive Care Unit - a Retrospective Clinical Analysis and Literature Search

Abstract: Background: Patients at intensive care units (ICUs) are often transfused to correct increased coagulation parameters (prothrombin time and activated partial thromboplastine time) and/or low platelet count. Thromboelastometry using whole blood is considered to be superior to these tests. In clinical praxis, prolonged standard tests are seen but thromboelastometry values are normal. The objective was to compare the blood product consumptions before and after the introduction of thromboelastometry assays into the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 18 publications
0
5
0
2
Order By: Relevance
“…44 In a retrospective study of 1879 ICU patients, there was a significant reduction in blood product use without any bleeding complications after the implementation of ROTEM prior to intervention. 45 In this study, if the prothrombin ratio was >1.5, the platelet count was >50 × 10 9 /L and the APTT ratio was <1.5, then ROTEM was performed. If the EXTEM CT was normal (40-80 s), then the procedure was performed without prophylactic FFP administration.…”
Section: Viscoelastic Testing: Thromboelastography (Teg) and Thromboe...mentioning
confidence: 94%
See 1 more Smart Citation
“…44 In a retrospective study of 1879 ICU patients, there was a significant reduction in blood product use without any bleeding complications after the implementation of ROTEM prior to intervention. 45 In this study, if the prothrombin ratio was >1.5, the platelet count was >50 × 10 9 /L and the APTT ratio was <1.5, then ROTEM was performed. If the EXTEM CT was normal (40-80 s), then the procedure was performed without prophylactic FFP administration.…”
Section: Viscoelastic Testing: Thromboelastography (Teg) and Thromboe...mentioning
confidence: 94%
“…As a consequence, FFP and platelet transfusion reduced by 35% and 3%, respectively in the first year and 52% and 20% in the second year after the introduction of ROTEM use. 45 Evidence has shown that TEG and ROTEM parameters predict blood loss during liver transplantation. [46][47][48] De Pietri et al randomised patients (60 patients with significant coagulopathy [INR >1.8/Platelets <50 × 10 9 /L]) to standard of care (FFP/platelet transfusion) or TEGguided transfusion prior to intervention.…”
Section: Viscoelastic Testing: Thromboelastography (Teg) and Thromboe...mentioning
confidence: 99%
“…There is evidence that use of ROTEM-guided haemostatic strategy reduces transfusion requirement in different clinical settings. [5][6][7] Understanding its limitations is equally important in the interpretation of ROTEM analysis. It is insensitive to the effect of platelet inhibitors such as aspirin and clopidogrel.…”
Section: Case Reportmentioning
confidence: 99%
“…Vyšetření ROTEM bylo prováděno u pacientů před invazivními výkony a malými chirurgickými zákroky. Normální výsledky ROTEM u pacientů, u nichž byly pozorovány patologické hodnoty standardních koagulačních testů, vedly ke snížení profylakticky podaných transfuzí čerstvě zmražené plazmy, eventuálně trombocytáního koncentrátu bez toho, aniž by došlo k rozvoji krvácivých komplikací, které by vyžadovaly chirurgickou revizi, byly patrné ultrazvukovým vyšetřením, či by vyžadovaly zavedení hrudní drenáže [16]. Podobným způsobem se podařilo snížit četnost transfuzí čerstvě zmražené plazmy či množství podaných koncentrátů protrombinového komplexu před invazivními zákroky nebo chirurgickými výkony u dospělých pacientů se sepsí [17] či u pediatrických pacientů s patologickými hodnotami PT, ale normálními výsledky ROTEM [18].…”
Section: Využití Rotem V Praxiunclassified
“…Týká se to nákladů pořizovacích i celkových, které v sobě zahrnují náklady na provoz, personál a spotřební materiál [29]. Dále díky ROTEM došlo ke snížení spotřeby transfuzních přípravků a tím k další finanční úspoře [16].…”
Section: Rotem V Perioperačním Období U Dětských Pacientůunclassified